The Molecular Epidemiology of Epizootic Hemorrhagic Disease Viruses Identified in Israel between 2015 and 2023 - Natalia Golender; Bernd Hoffmann (MDPI AG, 2024)
Epizootic hemorrhagic disease (EHD) is an infectious, non-contagious viral disease seriously affecting cattle and some wild ruminants and has a worldwide distribution. All viruses can be subdivided into "Eastern" and "Western" topotypes according to geographic distribution via the phylogenetic analysis of internal genes. In Israel, during the last decade, three outbreaks were registered: caused by EHDV-6 in 2015, by EHDV-1 in 2016, and by EHDV-7 in 2020. Additionally, RNA of EHDV-8 was found in imported calves from Portugal in 2023. During the same period in other countries of the region, non-Israeli-like EHDV-6 and EHDV-8 were identified. Full genome sequencing, BLAST, and phylogenetic analyses of the locally and globally known EHDV genomes allowed us to presume the probable route and origin of these viruses detected in Israel. Thus, EHDV-6 has probably been circulating in the region for a long period when EHDV-1 and -8 appeared here for the last years, while their route of introduction into the new areas was probably natural; all of them belonged to the "Western" topotype. In contrast, EHDV-7 probably had the "Eastern", anthropogenic origin. Data from the study can facilitate the evaluation of the appearance or reappearance of EHDVs in the Mediterranean area and enhance the planning of prevention measures.